Volume 4: Fluid Structure Interaction, Parts a and B 2006
DOI: 10.1115/pvp2006-icpvt-11-93703
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Laws for Model Test Based BWR Steam Dryer Fluctuating Load Definitions

Abstract: In recent years some Boiling Water Reactors have experienced significant steam dryer cracking. In some cases this cracking has necessitated unplanned outages to implement steam dryer repairs and has also resulted in de-rated operation of the affected units. In response to these recent steam dryer failures, GE has initiated a research program focused on identifying the nature of the fluctuating loads experienced by the steam dryer and developing predictive methods that can be used to develop load definitions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Howe 6) showed that the fluctuating pressure was proportional to u 3 =a (a, speed of sound) when there was a dipole acoustic source. Sommerville 7) applied the scale model to investigate flow-induced acoustic resonance at SRV stub pipes and showed that the fluctuating pressure was proportional to a 2 under the resonance condition. 7) In this study, u 2 =2 was applied to normalize the fluctuating pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Howe 6) showed that the fluctuating pressure was proportional to u 3 =a (a, speed of sound) when there was a dipole acoustic source. Sommerville 7) applied the scale model to investigate flow-induced acoustic resonance at SRV stub pipes and showed that the fluctuating pressure was proportional to a 2 under the resonance condition. 7) In this study, u 2 =2 was applied to normalize the fluctuating pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed inspection of the stem dryer showed that it was likely that the steam dryer had been damaged by high cycle fatigue due to acoustic-induced vibration [1,2]. The cause of the dryer's failure was considered as flow-induced acoustic resonance at the stub pipes of the safety relief valves (SRVs) on the main steam lines (MSLs).…”
Section: Introductionmentioning
confidence: 99%